(untitled) (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2026)
Cassava farmers will earn income from their farming business after harvesting 7-10 months later. With a fairly wide spacing of cassava plants (1-2 m), there is potential growing space under the cassava stands that can be intercropped with annual crops. In order for the intercrops planted with cassava to grow and produce optimally, it is necessary to arrange the layout of the sweet corn planting. In addition, information is also needed regarding sweet corn varieties that are suitable and adaptive for intercropping with cassava. This study aims to study the best sweet corn planting pattern that can produce growth and yield of sweet corn in an intercropping system, and to determine the best sweet corn varieties in the intercropping pattern of sweet corn with cassava. There are six combinations of planting treatments and sweet corn varieties. These treatments include: two layouts or planting positions of sweet corn, namely between cassava rows (J1) and within cassava rows (J2), and three commercial sweet corn varieties: Mira (V1), Paragon (V2), and Bonanza (V3). The results showed that sweet corn planted under cassava stands experienced a decrease in vegetative growth of 144 to 400% compared to sweet corn in a monoculture system, sweet corn planted between rows of cassava plants had better growth than those planted between rows of cassava, and sweet corn of the Bonanza variety was able to adapt better when intercropped with cassava.